The Relationship between The Teachers’ Demographics and Their Conflict Management Styles at Anuban Damrongrachanusorn School, Sisaket, Thailand - Bennagen, Markimson; Ye, Yan (Scholar: Human Sciences, 2016)
This study was conducted mainly to determine the correlation between the teachers’ demographics and their conflict management styles at Anuban Damrongrachanusorn School, Sisaket, Thailand in the academic year 2015. The demographics and the conflict management styles of the teachers were both surveyed and investigated by a questionnaire developed by Patana (2003). The demographics questionnaire surveyed the education background, age, and years of work experience while the conflict management styles questionnaire which was based on Thomas and Kilmann’s (2008) theory of conflict management investigated the conflict management styles of the teachers. Eighty- four full- time teachers at the school participated in the study. Various tools were used to calculate the data gathered for this study: descriptive statistics (Percentage and Mean) and Pearson Product- Moment Correlation Coefficient. The findings indicated that majority of the teachers were bachelor’s degree holders, 49 years old and below, and had at least 10 years of work experience. Moreover, the teachers’ conflict management styles, ranked from the highest to the lowest, were often compromising, often accommodating, often collaborating, occasionally avoiding, and occasionally dominating. Furthermore, the teachers’ conflict management styles as classified by their education background were accommodating and compromising; by their age were compromising and accommodating; and by their years of work experience were collaborating, compromising, and accommodating. Finally, there was no significant relationship between the teachers’ demographics and their conflict management styles at Anuban Damrongrachanusorn School, Sisaket, Thailand.